Kawin Kontrak dalam Perspektif Hukum Perdata dan Akibat Hukumnya - Tedi Siswanto, Cecep (DOKTRINA: JOURNAL OF LAW, 2024)
Marriage is considered sacred and eternal because individuals unite in a bond governed by law and moral values to form a happy family. In practice, there is a phenomenon of contract marriage that violates these principles. Contract marriage or contract marriage is an interesting issue to be studied in the context of civil law in Indonesia. This study examines how contract marriages in the perspective of Civil Law and their legal consequences. The research method used is a qualitative approach using data from primary and secondary legal materials. This research examines the phenomenon of contract marriage in the perspective of civil law, especially in the context of Indonesian law and its legal consequences. The results showed that the contract marriage agreement in civil law did not fulfill the validity requirements of the agreement in Article 1320, namely the objective requirements so that the contract marriage agreement was null and void. The legal consequences of the end of contract marriage result in the wife and children not having legal rights, legal protection, financial losses and difficulty accessing the rights that should be owned in a legally valid marriage.